Multiple organised haematomas in the presternal region of a cattle. Issue 1 (17th October 2013) - Alasonyalilar‐Demirer, A.; Kahraman, M. M.; Ipek, V.; Yildirim, B.
Abstract : This is the presentation of a case of numerous elastic masses with subcutaneous and mostly intramuscular localisation in the presternal region of a three‐year‐old dairy cattle. The masses were accidentally encountered at the meat inspection and submitted for further identification of their nature to the pathology department. Findings are presented here to make a contribution to the differential diagnosis from soft‐tissue neoplasms and ectopic trematode parasites when they are encountered at meat inspection or postmortem examination. To the best of the authors' knowledge, there has been no report on organised haematomas occurring at the presternal region of a cow except a textbook‐recorded case, which was reported in the hip muscle of a cattle.